Effects of Environmental Conditions on Pregnancy Rate in Replacement Beef Heifers - Oosthuizen, Nicola (J Anim Sci, 2021)
Five years of breeding records from Bos taurus replacement beef heifers (n = 21,134) were examined to quantify the effects of environmental conditions during the breeding season on first service pregnancy rate (PR) to artificial insemination (AI). Heifers were developed at Heartland Cattle Company in McCook, NE between April and July each year (2014–2018) where they were AI following estrus synchronization and detected estrus. Weather data were collected from a weather station located approximately 7.2 km from the research site, and included average, minimum, and maximum temperature and relative humidity (RH). Average daily temperature and RH were used to calculate average, minimum, and maximum temperature-humidity index (THI). Weather variables were analyzed for the week preceding AI, the day of AI, and for the week following AI (including the day of AI). Overall first service PR was 72.4% and ranged from 70.3 to 73.8% by year. On the day of AI, temperatures ranged from -15 to 40°C with a mean of 15.6°C ± 0.04. Positive linear relationships were determined for average, minimum, and maximum temperatures with PR for the week preceding AI (P ≤ 0.006), the day of AI (P ≤ 0.001), and the week following AI (P < 0.001). As average, minimum, and maximum temperature on the day of AI increased by 1°C, PR increased by 1.1, 1.0, and 0.7%, respectively. A positive linear relationship (P = 0.005) for maximum RH and a cubic relationship (P = 0.046) for minimum RH with PR were determined for the week preceding AI. Furthermore, positive linear relationships were determined for average, minimum, and maximum THI with PR for the week preceding AI (P ≤ 0.002), the day of AI (P ≤ 0.001), and the week following AI (P < 0.001). Therefore, temperature and THI during the breeding season may have a greater impact on pregnancy outcomes than RH. Linear effects demonstrate that increasing temperature, within the homeothermy zone, at the time of AI has a positive impact on PR.